Post-harvest treatment of vegetables with exometabolites of Nocardia vaccinii IMV B-7405, Acinetobacter calcoaceticus IMV B-7241 and Rhodococcus erythropolis IMV Aс-5017 to extend their shelf life - Pirog, Tatiana; Geichenko, Bogdana; Zvarych, Anna (My University, 2019)
The aim of the work was to study the possibility of Nocardia vaccinii IMV B-7405, Acinetobacter calcoaceticus IMV B-7241 and Rhodococcus erythropolis IMV Ac-5017 supernatants usage with various concentrations of surfactants for post-harvest treatment of vegetables. N. vaccinii IMV B-7405, A. calcoaceticus IMV B-7241 and R. erythropolis IMV Ac-5017 were grown on waste sunflower oil and ethanol. For vegetables treatment, supernatants of the culture broth with surfactant concentration of 0.01–0.5 g/l were used. The concentration of surfactants was determined by the gravimetric method after extraction with Folch mixture. The total number of heterotrophic bacteria and fungi on the surface of vegetables was determined by the Koch method on meat-peptone agar and wort agar, respectively. It was shown that treatment of broccoli, Brussels sprouts, sweet pepper and tomatoes with N. vaccinii IMV B-7405, A. calcoaceticus IMV B-7241 and R. erythropolis IMV Ac-5017 supernatants was accompanied by 6–17 and 8–50 times decrease of bacteria and fungi number on their surface, respectively, compared with that on the surface of vegetables washed with tap water. The possibility of double use of the same supernatant for various batches of vegetables washing was established. Non-treated and water-washed vegetables rotted faster than those treated with surfactant-containing supernatants. N. vaccinii IMV B-7405, R. erythropolis IMV Ac-5017 and A. calcoaceticus IMV B-7241 exometabolites used for treating vegetables to extend their shelf life have the following advantages in comparison with known microbial surfactants: they exhibit high antimicrobial activity when the surfactant concentration was several times lower and in the form of supernatant, which lets you exclude the expensive stage of isolation and purification of the target product from the technological process. In addition, surfactant-containing supernatants are highly effective in their repeated use. Метою роботи було вивчити можливість використання супернатантів Nocardia vaccinii ІМВ В-7405, Acinetobacter calcoaceticus ІМВ В-7241 та Rhodococcus erythropolis ІМВ Ас-5017 з різними концентраціями ПАР для післязбиральної обробки овочів. N. vaccinii IMV B-7405, A. calcoaceticus IMV B-7241 та R. erythropolis IMV Ac-5017 вирощували на відпрацьованій соняшниковій олії та етанолі. Для обробки овочів використовували супернатанти культурального бульйону з концентрацією ПАР 0,01–0,5 г/л. Концентрацію ПАР визначали гравіметричним методом після екстракції сумішшю Фольха. Загальну кількість гетеротрофних бактерій та грибів на поверхні овочів визначали методом Коха на м’ясо-пептонному агарі та сусло-агарі відповідно. Показано, що обробка брокколі, брюссельської капусти, солодкого перцю та томатів супернатантами N. vaccinii IMV B-7405, A. calcoaceticus IMV B-7241 та R. erythropolis IMV Ac-5017 супроводжувалася 6–17 та 8–50 разів зменшується кількість бактерій і грибків на їх поверхні відповідно в порівнянні з такою на поверхні овочів, промитих водопровідною водою. Встановлено можливість дворазового використання одного і того ж супернатанту для різних партій миття овочів. Необроблені та промиті водою овочі гнили швидше, ніж ті, що були оброблені супернатантами, що містять ПАР. Екзометаболіти N. vaccinii IMV B-7405, R. erythropolis IMV Ac-5017 та A. calcoaceticus IMV B-7241, які використовуються для обробки овочів з метою подовження терміну їх зберігання, мають наступні переваги порівняно з відомими мікробними поверхнево-активними речовинами: вони виявляють високу антимікробну активність, коли концентрація ПАР була в рази нижчою і у вигляді супернатанту, що дозволяє виключити з технологічного процесу дорогий етап виділення та очищення цільового продукту. Крім того, супернатанти, що містять поверхнево-активні речовини, є високоефективними при багаторазовому застосуванні.
Keywords: зберігання овочів; мікробне псування; поверхнево-активні речовини; кафедра біотехнології і мікробіології; storage of vegetables; microbial spoilage; surfactants